Brote de trichinellosis en la ciudad de San Antonio Oeste, Río Negro, en febrero de 2021 - Cortes, Maria Victoria; Llampa, Julio Argentino; Alder, Maite; Dacal Arriaga, Mariana Andrea; Seleiman, M.; Avila, A.; Fábrega, D.; Mora, M.; Rau, E.; Colombo, F.; Calabró, A.; Nahuelhual, Ada; et al. (Asociación Argentina de Producción Animal (AAPA), 2025)
Poster